1997
DOI: 10.1302/0301-620x.79b2.0790304
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Dislocation of the Hip During Convulsions

Abstract: Simultaneous bilateral posterior dislocation of the hip is very uncommon and most cases are caused by road accidents. Simultaneous bilateral posterior dislocation of the hip due to convulsions is extremely rare. We report the case of a man who was diagnosed late and operated on 15 weeks after the injury. We discuss the treatment of chronic dislocation of the hip and review the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Central acetabular fracture dislocation is seen following high velocity road traffic accidents and rarely following episode of seizures. 11 , 12 , 13 , 14 , 15 , 16 , 17 Rath et al 16 in 1997 suggested that the mechanism of injury around the hip joint following seizures is due to severe uncontrolled muscle contraction of proximal thigh muscle leading to strong force towards the hip joint. Other factor includes severe osteoporosis due to old age and anti-eplietic medications can lead to acteabular fracture and central dislocation of the hip joint following seizures episodes without direct traumatic event.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Central acetabular fracture dislocation is seen following high velocity road traffic accidents and rarely following episode of seizures. 11 , 12 , 13 , 14 , 15 , 16 , 17 Rath et al 16 in 1997 suggested that the mechanism of injury around the hip joint following seizures is due to severe uncontrolled muscle contraction of proximal thigh muscle leading to strong force towards the hip joint. Other factor includes severe osteoporosis due to old age and anti-eplietic medications can lead to acteabular fracture and central dislocation of the hip joint following seizures episodes without direct traumatic event.…”
Section: Discussionmentioning
confidence: 99%
“…Other factor includes severe osteoporosis due to old age and anti-eplietic medications can lead to acteabular fracture and central dislocation of the hip joint following seizures episodes without direct traumatic event. 1 , 2 , 11 , 12 , 13 , 14 , 15 , 16 , 17…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations